Analisa Pengaruh Kadar Abu (Ash Content) terhadap Nilai Kalor Batubara dengan Metode BS/ISO di PT Bukit Asam Tbk - Anggi Desri Elwiza; Miftahul Khair (MASALIQ, 2025)
Coal remains the primary energy source for power generation and industry; however, its quality is strongly influenced by ash content. Ash, as an inorganic mineral residue from combustion, reduces calorific value, thereby affecting energy efficiency and operational costs. This study aims to analyze the effect of ash content on coal calorific value based on BS/ISO standard methods. Coal samples were collected from several mining sites and tested in the laboratory to determine ash content through proximate analysis and calorific value using a bomb calorimeter. Data were analyzed quantitatively using correlation and regression tests to identify the relationship between ash content and calorific value. The results demonstrate a significant negative correlation, indicating that higher ash content corresponds to lower calorific value. Data visualization further illustrates a consistent decline in calorific value with increasing ash content, although anomalies appear in samples containing specific minerals. These findings underscore that ash content is a critical factor influencing coal quality and must be considered in its classification and utilization. The implications of this study provide valuable contributions for the mining industry and power plants in improving energy efficiency and promoting more optimal and sustainable coal utilization.